Enfrentamentos cotidianos das mulheres da comunidade de remanescentes de quilombolas do Cedro - Mineiros - GO - Silva, Aline Grigório da (2019)
This study was carried out in the southwestern region of Goiás, an area dominated by agribusiness. The objective of this study was to investigate daily practices, daily experiences, responsible for the production of commodities with high employment of technologies. It is in this scenario that the community of quilombola remnants of the cedar is inserted. The quilombola communities are scattered throughout the Brazilian territory, fighting and resisting to be able to remain in their territories. women are the main responsible for maintaining the identity traits of the community, which are directly linked to the relationship that residents have established over the years with the cerrado and medicinal plants. The methodological process to answer the objectives of this dissertation had a qualitative character and was developed based on Ethnography a methodology that allowed an approximation of the studied group, during the field work the data collection was made from semistructured interviews with the help of the field notebook which was fundamental for the registration of the researcher impression. It was noted that women in the community increased their participation in the labor market, but that it continues to lead the family. It was possible to find out that transformations are taking place in the patterns of values related to the sociocultural role of women. Women have been divided between domestic, social and political space. Demonstrating engagement to take leadership roles within and outside the community.